Summer temperature evolution on the Kamchatka Peninsula, Russian Far East, during the past 20000 years. - Meyer, Vera D; Hefter, Jens; Lohmann, Gerrit; Max, Lars; Tiedemann, Ralf; Mollenhauer, Gesine (PANGAEA, 2017)
Little is known about the climate evolution on the Kamchatka Peninsula during the last glacial?interglacial transition as existing climate records do not reach beyond 12 ka BP. In this study, a summer temperature record for the past 20 kyr is presented. Branched glycerol dialkyl glycerol tetraethers, terrigenous biomarkers suitable for continental air temperature reconstructions, were analyzed in a sediment core from the western continental margin off Kamchatka in the marginal northwest Pacific (NW Pacific). The record suggests that summer temperatures on Kamchatka during the Last Glacial Maximum (LGM) equaled modern temperatures. We suggest that strong southerly winds associated with a pronounced North Pacific High pressure system over the subarctic NW Pacific accounted for the warm conditions. A comparison with an Earth system model reveals discrepancies between model and proxy-based reconstructions for the LGM temperature and atmospheric circulation in the NW Pacific realm. The deglacial temperature development is characterized by abrupt millennial-scale temperature oscillations. The Bølling?Allerød warm phase and the Younger Dryas cold spell are pronounced events, suggesting a connection to North Atlantic climate variability.
Fractional abundances and concentrations of branched glycerol dialkyl glycerol tetraethers (brGDGT) of core SO201-2-12KL
Keywords: AWI_Paleo; Paleoenvironmental Reconstructions from Marine Sediments @ AWI